Electronic Communication in Plastic Surgery: Guiding Principles from the American Society of Plastic Surgeons Health Policy Committee. Issue 2 (February 2018) - Eberlin, Kyle R.; Perdikis, Galen; Damitz, Lynn; Krochmal, Dan J.; Kalliainen, Loree K.; Bonawitz, Steven C.
Abstract : Background: With the advancement of technology, electronic communication has become an important mode of communication within plastic and reconstructive surgery. This can take the form of e-mail, text messaging, video conferencing, and social media, among others. There are currently no defined American Society of Plastic Surgeons guidelines for appropriate professional use of these technologies. Methods: A search was performed on PubMed and the Cochrane database; terms included "telemedicine, " "text messaging, " "HIPAA, " "metadata, " "video conferencing, " "photo sharing, " "social media, " "Facebook, " "Twitter, " and "Instagram." Initial screening of all identified articles was performed; the level of evidence, limitations, and recommendations were evaluated and articles were reviewed. Results: A total of 654 articles were identified in the level I screening process; after more comprehensive review, 41 articles fit inclusion criteria: social networking, 12; telemedicine, 11; text messaging, 10; metadata, four; video conferencing, three; and Health Insurance Portability and Accountability Act, one. General themes were identified from these articles and guidelines proposed. Conclusion: Electronic communication can provide an efficient method of information exchange for professional purposes within plastic surgery but should be used thoughtfully and with all professional, legal, and ethical considerations. Abstract : Supplemental Digital Content is available in the text.